2015
DOI: 10.1016/j.bbrep.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional comparison of hexahistidine tagged and untagged forms of small multidrug resistance protein, EmrE

Abstract: EmrE is a member of the small multidrug resistance (SMR) protein family in Escherichia coli. EmrE confers resistance to a wide variety of quaternary cation compounds (QCCs) as an efflux transporter driven by proton motive force. The purification yield of most membrane proteins are challenging because of difficulties in over expressing, isolating and solubilizing them and the addition of an affinity tag often improves purification. The purpose of this study is to compare the structure and function of hexahistid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Despite this factor, all EmrE variants showed WT levels of resistance to one or more QCCs, highlighting the resilience of the protein to sequence variation. It should be noted that differences in ligand binding, protein folding, and MIC values for affinity-tagged EmrE and untagged EmrE were identified and suggested that untagged EmrE binds ligands (TPP, MV, ET, CPC) more tightly and conferred higher levels of drug resistance in a recent study (17). This highlights the importance of studying unmodified versions of a protein along with tagged constructs and now provides greater insight into the resistance conferred by native EmrE protein.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Despite this factor, all EmrE variants showed WT levels of resistance to one or more QCCs, highlighting the resilience of the protein to sequence variation. It should be noted that differences in ligand binding, protein folding, and MIC values for affinity-tagged EmrE and untagged EmrE were identified and suggested that untagged EmrE binds ligands (TPP, MV, ET, CPC) more tightly and conferred higher levels of drug resistance in a recent study (17). This highlights the importance of studying unmodified versions of a protein along with tagged constructs and now provides greater insight into the resistance conferred by native EmrE protein.…”
Section: Discussionmentioning
confidence: 89%
“…In an effort to examine the resistance attributed to conserved residues of unmodified EmrE, all variants were expressed in E. coli ΔacrB strains without an affinity tag. Our goal was to examine the resistance conferred by EmrE which had the least amount of modifications to avoid drug selection biases stemming from the affinity tag itself, as noted in a recent study (17). The vast majority of studies involving EmrE have involved the addition of an affinity tag (as reviewed in reference 1), specifically, a C-terminal myc-His 6 tag, which extends the protein by 30 amino acids and reduces its solubility but not membrane targeting (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to Glu14, aromatic residues have been shown to play a role in defining the active site: for example, Trp63 was demonstrated to be located close to the QCC binding pocket, and a variant of this residue abolished ligand binding [8] , [24] . Two other tryptophans are located within transmembrane segments 2 and 3 and a fourth tryptophan can be found in loop 2, all of which are expected to be involved in ligand interaction and can be used as spectroscopic probes of ligand binding [25] .
Fig.
…”
Section: Introductionmentioning
confidence: 99%